Analysis of Maximum Return Air Ratio on No-fogging Condition by In-cabin Climate Simulation for EV. (May 2017) - Liu, Jixuan; Zou, Huiming; Zhang, Guiying; Zhang, Xiaoqiang; Tian, Changqing
Abstract: Utilizing cabin return air to heat the cabin can reduce the heating load and save the battery power of Electric vehicle, but it is difficult to avoid fogging on the windshield caused by the high humidity of the return air. In this paper, the climate characteristics of the vehicle interior is analyzed by simulation with a thermal model based on the whole cabin. The simulation model is verified by an experimental test on a real car, and the errors are within 7%. The fogging conditions at different driving speeds and external air environments are drawn from the simulation results. An increase in external temperatures or a decrease in external humidity can benefit for increasing the return air ratio. The return air ratio decreases with the higher driving speed due to increases in the convective heat transfer coefficient, which leads to a lower temperature of the glass surface. This influence of the driving speed depends on the relative humidity of external air and becomes more obvious at the higher relative humidity conditions.